2022
DOI: 10.3389/fvets.2022.927499
|View full text |Cite
|
Sign up to set email alerts
|

Veterinary nursing in the United Kingdom: Identifying the factors that influence retention within the profession

Abstract: The UK regulatory body for registered veterinary nurses (RVNs), the Royal College of Veterinary Surgeons (RCVS), maintains the professional register of RVNs. Every year, a proportion fail to re-join the register. This research aimed to identify the factors that predict retention and to make recommendations to inform the Royal College of Veterinary Surgeons as the regulator as well as both the veterinary nursing and veterinary professions. An analysis of the raw quantitative data generated by the 2014 and 2019 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(20 citation statements)
references
References 26 publications
(36 reference statements)
1
19
0
Order By: Relevance
“…These include being recently qualified, having a lower salary, 4 having a lack of job satisfaction, having limited opportunities for career progression, being dissatisfied with employer support and feeling undervalued. 3 Similar reasons for attrition have also been reported by veterinary surgeons. [7][8][9][10] The understanding of the risk factors associated with veterinary nurse retention has, to date, been based on survey responses and often on the intention to leave the profession.…”
Section: Introductionsupporting
confidence: 63%
See 4 more Smart Citations
“…These include being recently qualified, having a lower salary, 4 having a lack of job satisfaction, having limited opportunities for career progression, being dissatisfied with employer support and feeling undervalued. 3 Similar reasons for attrition have also been reported by veterinary surgeons. [7][8][9][10] The understanding of the risk factors associated with veterinary nurse retention has, to date, been based on survey responses and often on the intention to leave the profession.…”
Section: Introductionsupporting
confidence: 63%
“…It has previously been reported that nurses who believe their career could progress are less likely to leave the profession. 3 'Career progression' was a commonly cited reason for nurses to resign in the present study, as recorded by the employees' line managers. The role of head nurse is a senior position within the nursing team; therefore, the lower odds of nurses in this position resigning suggests that open head nurse positions subsequently occur less frequently than other nursing roles, which could limit potential career progression opportunities for nurses.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations